Comparing Agentic Meritocratic Citizenship in Europe and China: A Research Note - Yasemin Soysal; Héctor Cebolla Boado (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Since the 1990s, global cultural shifts driven by neoliberalism have ushered in significant changes in the institutions of citizenship. This has given rise to an increasingly agentic conception of the individual, with strong meritocratic ideological underpinnings, as manifested across a wide range of policy and institutional domains. While the normative foundations and the institutional embodiment of agentic citizenship are widely studied, we know less about the individual enactments of such citizenship. We present comparative evidence on agentic and meritocratic orientations and their relationship with solidaristic inclinations among higher education students in China and Europe. – – Seit den 1990er Jahren hat der vom Neoliberalismus vorangetriebene globale kulturelle Wandel die Institutionen der Staatsbürgerschaft tiefgreifend verändert. Dies hat zu einem zunehmend agentischen Verständnis des Individuums auf Grundlage starker meritokratischer Ideologien geführt, was sich in diversen politischen und institutionellen Bereiche manifestiert. Obgleich die normativen Grundlagen und die institutionelle Ausgestaltung agentischer Staatsbürgerschaft weitgehend erforscht sind, bestehen nach wie vor substanzielle Wissenslücken hinsichtlich der individuellen Verwirklichung einer derartigen Staatsbürgerschaft. Dieser Artikel präsentiert vergleichende Forschungsergebnisse zu agentischen und meritokratischen Orientierungen unter Studierenden in China und Europa sowie dessen Beziehung zu solidarischen Neigungen
Keywords: 300; Agentic Citizenship; Meritocracy; Neoliberalism; Self-Efficacy; Redistributive Solidarity; Survey; Higher Education Students; Agentische Staatsbürgerschaft; Meritokratie; Neoliberalismus; Selbstwirksamkeit; Umverteilungssolidarität; Umfrageforschung; Studierende